Timing of banks' loan loss provisioning during the crisis - Leo de Haan; Maarten R. C. van Oordt (Bank of Canada, 2016)
We estimate a panel error correction model for loan loss provisions, using unique supervisory data on flow of funds into and out of the allowance for loan losses of 25 Dutch banks in the post-2008 crisis period. We find that these banks aim for an allowance of 49% of impaired loans. In the short run, however, the adjustment of the allowance is only 29% of the change in impaired loans. The deviation from the target is made up by (a) larger additions to allowances in subsequent quarters and (b) smaller reversals of allowances when loan losses do not materialize. After one quarter, the adjustment toward the target level is 34% and after four quarters is 81%. For individual banks, there are substantial differences in timing of provisioning for bad loan losses. We present two model-based metrics that inform supervisors on the extent to which banks' short-term provisioning behaviour is out of sync with their target levels.
Keywords: G01; G21; G32; 330; Financial institutions; Financial stability